Echocardiographic features of interventricular septal dissection in patients with Behçet's disease. Issue 2 (25th December 2018) - Yu, Shaomei; Han, Jiancheng; Gao, Shuang; Ruan, Yanping; Gu, Xiaoyan; Sun, Lin; He, Yihua
Abstract : Involvement of the heart in Behçet's disease (BD) is rare. We retrospectively analyzed these three patients with interventricular septal (IVS) dissection in BD and discussed the echocardiographic manifestations of IVS dissections. In our patients, the echocardiographic characteristics of IVS dissection were echo‐free space in the IVS basal segment or basal to middle segment, dilatation in the diastole and contraction in systole, and abnormal turbulent blood flow in the heart.